2009
DOI: 10.1111/j.1469-0691.2009.02851.x
|View full text |Cite
|
Sign up to set email alerts
|

International diagnostic accuracy study for the serological detection of chikungunya virus infection

Abstract: External quality assurance for serological detection of chikungunya virus infection was performed to assess the diagnostic quality of expert laboratories. Of 30 participants, only six correctly analysed all reference samples with their respective tests. Thirteen laboratories gave at least 85% correct results, and 11 laboratories 75% or less. IgM antibodies were detected less frequently than IgG antibodies (p <0.001). The study provides information on the quality of different serological tests and indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
0
25
1
1
Order By: Relevance
“…However, IgG antibodies are reported to be detectable in convalescence and remains so for years (Chia et al 2010). A recent multi-country study carried out reported the better utility of IgG in detection of chikungunya infection compared to IgM (Niedrig et al 2009). Knowledge about the kinetics of the serological markers of CHIKV infection has been recently reviewed (Schwartz & Albert 2010).…”
mentioning
confidence: 99%
“…However, IgG antibodies are reported to be detectable in convalescence and remains so for years (Chia et al 2010). A recent multi-country study carried out reported the better utility of IgG in detection of chikungunya infection compared to IgM (Niedrig et al 2009). Knowledge about the kinetics of the serological markers of CHIKV infection has been recently reviewed (Schwartz & Albert 2010).…”
mentioning
confidence: 99%
“…The detection of CHIKV-RNA, based on detection of viral nucleic acid in serum samples by reverse-transcriptase PCR, results positive during the first week after symptom onset (viremic phase) and has an excellent sensitivity and specificity [22]. The indirect methods are based on antibody detection: Anti-CHIKV antibodies can be usually detected 5 days after symptom onset for IgM and a few days later for IgG [7,23]. False positive and false negative results are possible, due to cross-reactivity with other viruses of the same family and to mixed cryoglobulinemia induced by CHIKV, respectively [7,24].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial and inhouse serologic assays, such as the hemagglutination inhibition assay (offered by the National Microbiology Laboratory), enzyme immunoassays or immunofluorescence assays, which detect circulating IgG antibodies to chikungunya virus and are reported to have varying sensitivities and specificities. 9 Generally, assays detecting IgG antibodies have superior performance to those detecting IgM. 9 Immuno globulin M antibodies become detectable within two to six days of symptom onset and persist for weeks to months, whereas IgG antibodies first appear during convalescence and can persist for years.…”
Section: Diagnosismentioning
confidence: 99%
“…9 Generally, assays detecting IgG antibodies have superior performance to those detecting IgM. 9 Immuno globulin M antibodies become detectable within two to six days of symptom onset and persist for weeks to months, whereas IgG antibodies first appear during convalescence and can persist for years. …”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation